Evaluation of the Integrated Marine and Fisheries Center Development Program in Natuna Regency - Wiwik Susanto; Sinung Rahardjo; Subekti Nurmawati (Hasanuddin University, 2025)
This study aims to evaluate the implementation of the Integrated Marine and Fisheries Center Development Program (Sentra Kelautan dan Perikanan Terpadu or SKPT) in Natuna Regency, focusing on its benefits for fishers and coastal communities. A descriptive qualitative approach was used, involving in-depth interviews, observations, and documentation. The results show diverse perspectives among stakeholders. Some fishers and cooperative managers perceive the SKPT as beneficial in expanding market access and maintaining product quality; however, limited capital, low post-harvest skills, and weak institutional readiness remain major challenges. Meanwhile, officials from the Department of Marine and Fisheries and SKPT managers emphasize the need to improve inter-institutional coordination and landing regulations to optimize the program's effectiveness. The study also reveals protests and resistance from coastal communities, particularly traditional fishers, who feel disadvantaged due to reduced fishing zones and unequal distribution of aid. Furthermore, academic assessments indicate that the program’s success remains partial, with significant physical achievements but limited impact on broad economic welfare improvements. Based on these findings, it is concluded that the success of the SKPT requires a participatory approach, strengthening of local capacity, and continuous evaluation based on comprehensive evaluation models such as CIPP. The implications of this study highlight the importance of aligning physical, social, and economic development to achieve the goals of independence and sustainable welfare for Natuna’s coastal communities.